Symptomatic Wingspan stent stenosis and occlusion: stent-in-stent rescue. (4th June 2010) - Le, Tri M; Gaughen, John R; Jensen, Mary E; Evans, Avery J
Abstract : The use of the Wingspan stent in severe intracranial stenosis is associated with a relatively high in-stent re-stenosis rate. Reported management strategies for re-stenosis have included angioplasty alone or angioplasty with placement of a second Wingspan stent. A case is presented in which thrombosis within a Wingspan stent was treated with a balloon expandable cobalt-chromium stent within the Wingspan stent. Subsequent follow-up imaging has shown persistent patency of the treated vessel, with no subsequent in-stent stenosis.